A radomised controlled trial evaluating family mediated excercise (fame) therapy following stroke - Galvin, Rose (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Physiotherapy, 2010)
The aim of this study was to examine the impact of additional family mediated exercise (FAME) therapy on outcome of the lower limb (LL) following acute stroke through the implementation of a randomised controlled trial (RCT). Outcome was assessed at the level of impairment, activity and participation. A secondary aim of the study was to evaluate the impact of the FAME programme on the person with stroke and the family member assisting in the delivery of the exercises to them through qualitative and quantitative data gathering techniques.
Keywords: Physiotherapy, Ph.D.; Ph.D. Trinity College Dublin